Quadrature Frequency Generation for Wideband Wireless Applications - Elbadry, Mohammad (Springer, 2016)
This book describes design techniques for wideband quadrature LO generation for software defined radio transceivers, with frequencies spanning 4GHz to around 80GHz. The authors discuss several techniques that can be used to reduce the cost and/or power consumption of one of the key component of the RF front-end, the quadrature local oscillator. The discussion includes simple and useful insights into quadrature VCOs, along with numerous examples of practical techniques.